Vaccination against Pneumococcal Infections of High-Risk People: Pharmacoeconomic Aspects - A. V. Rudakova; S. M. Kharit; Yu. V. Lobzin (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Vaccination of people at high risk against pneumococcal infection with a 13-valent conjugate vaccine (PCV13) can significantly reduce the corresponding incidence and mortality.The aim of the work was to assess the pharmacoeconomic aspects of vaccination of 65 year olds with a high risk of pneumococcal infection.Material and methods. The analysis was carried out by the method of Markov modeling from the position of the health care system. The time horizon is 5 and 15 years. It was assumed that vaccination is carried out with 1 dose of PCV13 and 1 dose of polysaccharide pneumococcal vaccine (PPV23) after 8 weeks with revaccination with 1 dose of PPV23 after 5 years. The costs of treatment of pneumococcal infections were calculated on the basis of the Compulsory medical insurance rates for St. Petersburg in 2019. The costs of vaccination were calculated on the basis of the price of auctions for the purchase of PCV13 and PPV23 for 2019.Results. For 15 years, vaccination of 100 ths people from the high risk group will prevent 1.7 ths cases of community-acquired pneumonia, 1.4 ths cases of invasive pneumococcal infections, and 397 cases of pneumococcal infections deaths. The cost-effectiveness ratio with a 15-year horizon is 161.4 ths rubles/quality-adjusted life year gained (QALY). Even if the time horizon is reduced to 5 years, vaccination can be considered as an economically highly effective intervention (cost-effectiveness ratio –571.9 ths rubles/QALY). At the same time, in 5 years, 37.6% of the money spent on vaccination will be returned to the budget of the health care system, and in 15 years – 49.3%.Conclusion. Vaccination of citizens of the Russian Federation from a high-risk group against pneumococcal infection can be considered as a socially and economically highly effective intervention that provides a significant reduction in the incidence and mortality caused by it.